Environmental sustainability analysis of charcoal production in Mulanay, Quezon, Philippines - Inzon, Maria Rowena Beatriz Q. (Journal of Environmental Science and Management, 2016)
Global and historical trends show the re-emergence of wood fuels as alternative sources of energy amid concerns over their environmental impacts. Charcoal production, in particular, remains a significant source of indigenous energy for developing countries like the Philippines, where it is perceived as a cause of deforestation and environmental degradation. This study presents a case where charcoal production can be practiced on a sustainable basis by focusing on aspects that affect the environment, namely, wood source, harvesting strategy and production techniques. Key informant interviews, focus group discussions and a survey among charcoal producers in Mulanay, Quezon revealed a preference on hardwoods that produce slow burning charcoals and other readily-available, usually invasive, tree species. Harvesting strategies include tree felling and pruning and rotational harvesting to allow stock replenishment. Charcoal producers employ an old but simple production technique called 'binulkan', which has an efficiency rate of 7.7% by weight. The study concludes that an environmentally-sustainable charcoal industry in Mulanay can be achieved by planting and utilizing suitable tree species and improving harvesting systems and production techniques. Further study, is recommended to assess the feasibility of establishing wood plantations for charcoal production with regard to its poverty reduction potential and continued benefits to the community.